Optimizing Endothelial Targeting by Modulating the Antibody Density and Particle Concentration of Anti-ICAM Coated Carriers - Calderon, Andres (2010)
Targeting of drug carriers to cell adhesion molecules expressed on endothelial cells (ECs) may improve treatment of diseases involving the vascular endothelium. This is the case for carriers targeted to intercellular adhesion molecule 1 (ICAM-1), an endothelial surface protein overexpressed in many pathologies. In order to optimize our design of anti-ICAM carriers, we have explored in this study the influence of two carrier design parameters on specific and efficient endothelial targeting in vitro and in vivo: carrier dose and density of targeting molecules (antibodies -Ab-) on the carrier surface. Using radioisotope tracing we assessed the role of these parameters on the biodistribution of model polymer carriers targeted to ICAM-1 ((125)I-anti-ICAM carriers) in mice. Increasing the carrier dose enhanced specific accumulation in the lung vasculature (a preferential endothelial target) and decreased non-specific hepatic and splenic uptake. Increasing the Ab density enhanced lung accumulation with minimally reduced liver and spleen uptake. These studies account for the influence of blood hydrodynamic forces on carrier binding to endothelium, relevant to arterioles, venules and larger vessels. Yet, carriers may rather bind to the extensive capillary bed where shear stress is minimal. We used fluorescence microscopy to determine binding kinetics of FITC-labeled anti-ICAM carriers in static conditions, at the threshold found in vivo and conditions mimicking low vs high ICAM-1 expression on quiescent vs activated ECs. Binding to activated ECs reached similar saturation with all tested Ab densities and carrier concentrations. In quiescent cells, carriers reached ~3-fold lower binding saturation, even at high carrier concentration and Ab density, and carriers with low Ab density did not reach saturation, reflecting avidity below threshold. Binding kinetics was positively regulated by anti-ICAM carrier concentration and Ab density. Counterintuitively, binding was faster in quiescent ECs (except for carriers with high Ab density and concentration), likely due to fast saturation of fewer binding sites on these cells. These results will guide optimization of ICAM-1-targeted carriers, e.g., in the context of targeting healthy vs diseased endothelium for prophylactic vs therapeutic interventions.